Managing student workload in clinical simulation: a mindfulness-based intervention - Pollard, Cheryl; McKendrick-Calder, Lisa; Shumka, Christine; McDonald, Mandy; Carlson, Susan (My University, 2019)
Background: Simulation places multiple simultaneous demands on participants. It is well documented in the literature that many participants feel performance stress, anxiety or other emotions while participating in simulation activities. These feelings and other stressors or distractions may impact participant ability to engage in simulation. The use of mindfulness has been proven to enhance performance in other contexts and we wondered if including a mindful moments activity in the traditional pre-brief would change the participants perceived workload demands. Method: Utilizing a 4th year undergraduate nursing course with intense simulation requirement we were able to compare a control group to an intervention group who was exposed to this mindful moment activity. All participants completed the same simulations. Post-simulation event, all participants completed the National Aeronautics and Space Administration Task Learning Index which measures mental demands, physical demands, temporal demands, effort, performance and frustration. Our convenience sample consisted of 107 nursing students (86 treatment group, 21 control group) who participated in 411simulations for this study. Results: The control group experienced significantly different perceived workload demands in two domains (temporal and effort). Conclusion: It is possible to manipulate participants’ perceived workload in simulation learning experiences. More research is needed to determine optimal participant demand levels. We continue in our practices to utilize this technique and are currently expanding it to use in other high stress situations such as before exams.
Keywords: simulation; stress; mindfulness; nursing education; disorienting dilemma; mental demands; physical demands; temporal demands; performance anxiety; frustration; simulation design